Bulgaria Financial Sector Assessment Program : Stocktaking of Progress Achieved by the Bulgarian National Bank in Strengthening Banking Supervision - International Monetary Fund; World Bank (World Bank, Washington, DC, 2017)
This technical note (TN) provides a stocktaking of the current state of the implementation of the key recommendations made by the IMF and the World Bank in their 2015 assessment report on the observance of Basel Core Principles (BCPs) for effective banking supervision in Bulgaria. It provides an overview of the most recent initiatives taken by the Bulgarian National Bank (BNB) to address the shortcomings found in the domestic supervisory regime. It also reflects the regulatory and supervisory framework in place as of the date of the completion of this review. This note does not provide an exhaustive analysis of each of the 29 BCPs and is not meant to revise the ratings assigned by the BCP assessors in their 2015 report. The focus is on the eight principles that were found to be materially non-compliant in 2015. In addition, there is analysis of the progress achieved on six principles rated as largely compliant in 2015 that have an important bearing on the effectiveness of supervision and where the BNB is working to enhance its supervisory practice.